Microwave Assisted Synthesis of Monoazanaphthalene Scaffolds - Cieslik, Wioleta; Serda, Maciej; Kurczyk, Agata; Musiol, Robert (Current Organic Chemistry, 2013)
Current achievements in the microwave-assisted synthesis of quinoline and isoquinoline are discussed in this review. Monoazanaphthalenes are important scaffolds in organic synthesis and especially in drug design. Due to their frequent appearance in biologically active compounds, drugs and natural products, they are claimed to be privileged structures. Synthetic routes to these compounds have been known for more than one hundred years but their availability is still the main limiting factor. Conventional methods are laborious, time consuming and do not offer satisfactory yields or purity of the products. On the other hand, microwave-assisted protocols do not provide enough versatility in designing a molecular scaffold, i.e. substitution pattern. Most of the known microwave-assisted syntheses consist of the modification of monoazanaphthalene rings and as such are limited to several easily available scaffolds.
Keywords: Organic synthesis